Quantifying Severity of Preschool-Aged Children's Internalizing Behaviors: A Daily Diary Analysis. (January 2023) - Bufferd, Sara J.; Olino, Thomas M.; Dougherty, Lea R.
A subset of preschool-aged children meets criteria for impairing and persistent anxiety and depression. However, the overlap between normative emotional development and impairing symptoms complicates assessments of internalizing problems in early childhood. Given the benefits of early identification/prevention and avoiding overpathologizing typical development, empirical information is needed to norm expression of internalizing behaviors. In this 14-day online diary study, 609 primary caregivers of 3- to 5-year-old children reported the frequency of children's daily separation and social anxiety and depressive behaviors and impairment. Item response theory analyses quantified specific frequencies at which each behavior was psychometrically severe/rare. Patterns varied for each behavior; for example, distress when anticipating separation had to occur at least 10 times and sadness at least 35 times over 14 days to be considered severe. Most social anxiety behaviors had to occur approximately every other day to be considered severe. Parameters did not vary by child age or sex, and behaviors were significantly associated with impairment. These data provide empirical information for refining internalizing behavior assessment in preschool-aged children and can be used as benchmarks by child practitioners to assess the extent to which frequencies fall in the range of developmentally typical behavior versus those that may be more severe.